Permainan Edukasi Tebak Nama Pahlawan Nasional Menggunakan WEB di SDN Cikancung 1 - Jaelani, Jaelani; Hidayatulloh, Syarif (Teknik Informatika Universitas Pamulang, 2021)
Learning history, especially about national heroes, is the first thing that needs to be done to instill the value of struggle and is a moral lesson for students at school. Observations that the author made on students in the SDN Cikancung 1 environment, the problem obtained was that there was so much material that had to be memorized and the lecture learning method applied at this time made students less interested and bored quickly. So the purpose of this research is to create a WEB-based question-and-answer educational game on the names of national heroes using the GDLC method for grade 4 SDN Cikancung 1. GDLC (game development life cycle) is a step-by-step approach to analyzing and building games using a specific cycle and more complex. The GDLC method is used as a research method in making this game, where the research stages consist of initiation, pre-production, production, testing, beta, and release. The results of this study indicate that students as game users judge that they can operate this game easily, helping the learning process to be more interesting than the previous learning process as well as making teachers and students more creative and innovative in the learning process at school.